Collaborative administration: the management of successful networks. Issue 3 (16th March 2017) - Cristofoli, Daniela; Meneguzzo, Marco; Riccucci, Norma
ABSTRACT: Despite a general consensus on the importance of collaborative settings for the solution of 'wicked' problems, questions of how to successfully manage public networks remain without a clear answer. Some authors highlighted the importance of the network structure and context; other authors shed light on network management and coordination mechanisms. More recently, some scholars have stressed the criticality of 'soft' factors, such as interorganizational trust. In this multifaceted landscape, the goal of the special issue is to stimulate a dialogue on the functioning of public networks, and contribute to the development of sound knowledge about how to make them succeed.